Implementation of Sharia Economics in Indonesian Banking - Azriel Mohamad Yapanto (International Journal on Economics, Finance and Sustainable Development, 2022)
The implementation of the sharia economy is not only focused on banking. Sharia economics is intended to provide an overall economic benefit, including in managing finances. The goal is to socialize the sharia economy which is engaged in managing or managing sharia finance in an effort to improve financial planning and help resilience in the impact of the economic crisis. The method is qualitative in the use of descriptive data analysis techniques. There is still a lack of information or in-depth understanding of the teachings in Islam regarding the economy, especially sharia financial management, which is known to the Indonesian people, who are predominantly Muslim. Because of the provisions of both prohibitions and obligations in Islamic financial management.